Unlocking the spell : a tale of the wide-awake princess - Baker, E. D. (Bloomsbury, 2012)
Princess Annabelle, who is immune to magic and can temporarily reverse spells put on others, encounters various fairy tale characters when she embarks on an expedition into the woods to find a dwarf responsible for turning Sleeping Beauty's prince into a bear.